2020
DOI: 10.3390/molecules25112638
|View full text |Cite
|
Sign up to set email alerts
|

(‒)-Cannabidiolic Acid, a Still Overlooked Bioactive Compound: An Introductory Review and Preliminary Research

Abstract: Cannabidiolic acid (CBDA) is the main phytocannabinoid in fiber and seed-oil hemp (Cannabis sativa L.) plants, but its potential health-related capabilities have been masked for years by a greater scientific interest towards its neutral derivative cannabidiol (CBD). This review aims to collect from the literature and critically discuss all the information about this molecule, starting from its biosynthesis, and focusing on its bioactivity, as an anti-inflammatory, anti-emetic, anti-convulsant, and anti-cancero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 65 publications
0
40
0
Order By: Relevance
“…Based on comparison with a pure reference compound, previously isolated and chemically characterized by means of spectroscopic and spectrometric techniques [ 14 ], the compound eluting at the lower retention time (A; 16.8 min) was identified as cannabidiolic acid (CBDA-C5). This latter is the acidic phytocannabinoid mainly produced by industrial Cannabis sativa L. plant varieties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on comparison with a pure reference compound, previously isolated and chemically characterized by means of spectroscopic and spectrometric techniques [ 14 ], the compound eluting at the lower retention time (A; 16.8 min) was identified as cannabidiolic acid (CBDA-C5). This latter is the acidic phytocannabinoid mainly produced by industrial Cannabis sativa L. plant varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Phytocannabinoids, chlorogenic acids and caffeine were quantified in coffee drinks by means of the external standard method. The reference standards caffeine, cannabidiol (CBD) and 5-O-caffeoylquinic acid (5-CQA) were purchased from Sigma-Aldrich (Milan, Italy), whereas CBDA and THCA were previously isolated in our lab [14]. For this purpose, calibration curves were constructed (Table 1), injecting working solutions of each standard, prepared by dilution from a stock solution, into the UHPLC-ESI-QqTOF MS system under the same conditions as the samples.…”
Section: Quantification Of Phytocannabinoids Chlorogenic Acids and Cmentioning
confidence: 99%
“…This finding is in line with previous studies on Cannabis resin and inflorescences ( Lindholst, 2010 ; Peschel, 2016 ). Although the major therapeutic knowledge on Cannabis focuses on phytocannabinoids in their decarboxylated form, several recent studies report on the pharmacological activities of several acid phytocannabinoids ( Bolognini et al, 2013 ; Rock and Parker, 2013 ; Rock et al, 2013 , 2018 ; Nallathambi et al, 2017 ; Anderson et al, 2019 ; Formato et al, 2020 ). Several in vivo studies even revealed that CBDA is a considerably more potent antiemetic agent than the well-studied CBD (1000 times more potent; Bolognini et al, 2013 ; Rock and Parker, 2013 ) and is also a more potent anticonvulsant agent (10 times more potent; Anderson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabidiolic acid, the main phytocannabinoid compound in fiber and seed-oil plants, was detected and quantified by means of its HPLC-UV features [54]. Although the nutraceutical value of this compound is still far from being achieved, its high content in hemp varieties cultivated for food purposes, suggests the need for a deeper understanding of its detection and quantification, and to address its content assessment as a quality feature of hemp seed oil.…”
Section: Cannabidiolic Acid Content Of Investigated Hemp Seed Oilsmentioning
confidence: 99%
“…Cannabidiolic acid (CBDA) content was estimated by HPLC-UV-DAD analysis according to Formato et al [54]. To this purpose, the HPLC 1260 INFINITY II system (Agilent, Santa Clara, CA, USA) was utilized, equipped with an Agilent G7129A autosampler, an Agilent GY115A DAD-UV-visible detector and a Quaternary pump Agilent G711A.…”
Section: Cannabidiolic Content Determinationmentioning
confidence: 99%